Manhole intrusion detection system with notification stages - Mazunga, Felix; Romosi, Tawanda; Guvhu, Rosemary (Scientific African, 2021)
Appropriate design of intrusion detection systems is extremely important to safeguard critical and valuable infrastructure. Telecommunications companies (TELCOs) and electric power utilities are experiencing an increased rate of rampant underground copper cable theft and vandalism. This paper addresses the important subject of combating the physical intrusion of critical infrastructure by proposing a low-cost, effective and unique manhole intrusion detection system. Manholes are openings to confined underground spaces that are used to access critical underground infrastructure and utilities such as sewer systems, electricity and telecommunication networks for maintenance and inspection. Critical infrastructure protection is very essential to avoid losses and incapacitations that would have a debilitating effect on economic activities, security, public health and safety, and so on. The increasing rate of rampant copper theft and vandalism could be attributed to the increased demand and high prices for copper on the black market. Critical infrastructure sectors such as TELCOs, electricity supply, water and rail transport are utilizing intrusion detection systems that only trigger an alarm when the critical infrastructure has already been vandalized or stolen. In this paper, we propose a low-cost and unique manhole intrusion detection system with notification stages devoted to safeguard critical infrastructure. Simulations of the system were performed before hardware implementation. The proposed system utilizes an Arduino Uno microcontroller and multiple sensors to trigger the intrusion stages early before the copper cables are vandalized. Due to the inclusion of three different additional sensors, the proposed system has an advantage of timely or early-stage intrusion detection. The response time is improved since the first alert is sent early before the actual cutting of the cable. The GSM messaging system is utilized as the alert mechanism during the intrusion stages. Notifications are also displayed on a local LCD.